Towards an advanced impact analysis of intangible resources in organisations - Andrea Fried; Volker Linss (Technische Universität Chemnitz, Lehrstuhl für Innovationsforschung und nachhaltiges Ressourcenmanagement, 2005)
The paper refers to the discussion of measuring and assessing knowledge capital. In particular, the interconnectedness of the intangible resources in organizations is not well represented in the methodical approaches. Moreover, the identification of driver resources which is strongly connected with this question is far from being solved in a satisfactory manner. Therefore, this article reviews existing methods of the scenario analysis in view of the performance measurement discussion and contributes towards an advanced analysis of resources in organizations.
urn:nbn:de:swb:ch1-200501203
Keywords: 330; ADVIAN method; driver; impact analysis; intangible resource; knowledge capital; MICMAC method; performance measurement system